Availability of Sexually Transmitted Disease and HIV Clinical Services: Ending the HIV Epidemic Versus Non–Ending the HIV Epidemic Jurisdictions, 2018. Issue 1 (24th January 2022) - Leichliter, Jami S.; Cuffe, Kendra M.; Kelley, Kathleen R.; Gift, Thomas L.
Abstract : We found that the availability of most sexually transmitted disease/HIV services, other than HIV testing, did not differ by Ending the HIV Epidemic jurisdiction status and is lacking for sexually transmitted disease/HIV prevention needs. Supplemental digital content is available in the text. Abstract: We assessed sexually transmitted disease/human immunodeficiency virus (HIV) service availability at the primary sexually transmitted disease safety net clinic by phase I Ending the HIV Epidemic jurisdiction status. HIV testing was >90%. In Ending the HIV Epidemic jurisdictions, 22% of primary safety net clinics initiated and/or provided preexposure prophylaxis (PrEP), 46.6% provided PrEP education or referral only, and 29.9% did not provide any PrEP services.